New taxonomic twists in shore flies as revealed in discovery of Neozealides, a new genus from New Zealand (Diptera: Ephydridae) - Mathis, Wayne N.; Zatwarnicki, Tadeusz (Zootaxa, 2019)
We describe Neozealides to accommodate two endemic species from New Zealand that were previously placed in the shore-fly genus Hyadina Haliday. Although similar to Hyadina, both species are more closely related to the Hyadina and Philygria groups of genera (Zatwarnicki & Ryczko 2014) than they are to species within Hyadina. To document these discoveries, we revise both species, placing them in Neozealides. Emphasis is given to structures of the male terminalia, which are fully illustrated. Detailed locality data and distribution maps for both species are provided. For perspective and to facilitate recognition of genera, the tribe Hyadinini is diagnosed and a key to genera from New Zealand is provided.